A COMMUNITY-BASED VULNERABILITY ASSESSMENT OF FLOODS IN URBAN AREAS OF KAMPUNG MELAYU, JAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Flooding has become a serious problem in Jakarta. During floods .of 2007, Kampung Melayu, East Jakarta was the worst hit.by the floods. Community have different perceptions on disaster and have different effort to overcome the hazards. Therefore, local government and relevant institution should investigate this situation and make this information a valuable input in developing and implementing response plans in flood mitigation. This research is to explore the vulnerability of floods based on local people's perception. There were 83 households interviewed using questionnaire. Certain elements at risk related with physical and socio:economic aspects were identified. Physical information concerned the building structure and building contents. Several socio-economic characteristics were used as key indicators to analyze the vulnerability of people. Generally, the result of this research shows that the ability of people to cope with the flooding i$ linked with the capacity of the people itself. The capability of people to deal withflooding was influenced by several indicators.based on their socio- . economic characteristics. For example, lower income people will experience more suffering than the wealthier, because they cannot afford the' costs of repair, reconstruction. Although the wealthier are likely to experience a higher degree of economic damage due to possessions of higher value. Base on the analysis, all coping strategies and flood measures are not enough to cope with flooding in the study area.